The inviolability of parliamentary Chambers in the Spanish legal system: meaning and scope - Luis (Journal of the Basque Parliament, 2022)
Attempts to restrict the free functioning of the Chambers are part of the history of parliamentarism. For this reason, the protection of the free functioning of Parliaments and the space in which they carry out their functions constitute essential guarantees of the functioning of representative democracy, which in the tradition of parliamentary law integrate the so-called prerogatives or privileges of the Chambers and which found explicit recognition in the Spanish Constitution of 1978, whose article 66.3 proclaims that “The Cortes Generales are inviolable”. A relatively original provision in comparative law and novel in our constitutional tradition that was also incorporated into the different Statutes of autonomy of the Autonomous Communities. The purpose of this work lies in unraveling the meaning and scope of the constitutional and statutory guarantee of the inviolability of the Chambers in the legal system of the Spanish State and its connection with other elements of the institutional design of the legislative Assemblies.